PENGARUH KEBIJAKAN MONETER TERHADAP PEREKONOMIAN INDONESIA - Indah Nur Aliza; Andira Putri Balkis; Apriliantoni (Cahaya Ilmu Bangsa, 2024)
Abstract This research analyzes the effect of inflation on Indonesia's economic growth in 2023-2024. On the other hand, monetary policy is a strategy to adjust macroeconomic conditions so that they are as useful as possible by regulating the amount of money available for trading. According to data from the Central Statistics Agency (BPS), Indonesia's inflation in January 2024 was 0.04 percent on an annual basis, while inflation in January 2024 was 2.57 percent on an annual basis. By the end of January 2024, food prices had risen 26.27% and by the end of December 2023 they had risen 0.9%. The interest rate decision in August 2024. Keywords : Indonesian economy, monetary policy, inflation and interest rates. Abstrak Penelitian ini menganalisis dampak inflasi terhadap pertumbuhan ekonomi Indonesia tahun 2023 hingga 2024. Kebijakan moneter, di sisi lain, adalah strategi untuk menyesuaikan kondisi. Makroekonomi bertujuan untuk mencapai kegunaan yang dimaksudkan dengan mengatur jumlah uang yang tersedia untuk transaksi. Laju inflasi Indonesia naik pada bulan Januari, menurut Badan Pusat Statistik (BPS) 2024 adalah 0,04 persen secara tahunan, sementara inflasi pada Januari 2024 adalah 2,57 persen secara tahunan. Pada akhir Januari 2024, harga pangan sudah naik 26,27% dan pada akhir Desember 2023 naik 0,9%. Keputusan suku Pada bulan Agustus 2024. Kata kunci : perekonomian Indonesia, kebijakan moneter, inflasi dan suku bunga.